2014
DOI: 10.1039/c4ra10177d
|View full text |Cite
|
Sign up to set email alerts
|

Highly sulfonated graphene and graphene oxide nanosheets as heterogeneous nanocatalysts in green synthesis of bisphenolic antioxidants under solvent free conditions

Abstract: Sulfonated functionalized graphene and graphene oxide nanosheets were prepared via chemical approaches and their catalytic activities were investigated in the green synthesis of 6,6′-(arylmethylene)bis(2,4-dialkylphenol) antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Moreover, in an effort to seek improved yields, the catalytic amount of GO‐SiPr‐SO 3 H was screened (Figure ). As shown in this Figure, the 0.85 mol% (20 mg) of the catalyst showed the best result for compound 3 a (96 %, 3.5 min, TOF: 969 (h −1 ), (US irradiation); vs 68 %, 70 min, TOF: 6.9 (h −1 ) (heating method). The TOF of the GO‐SiPr‐SO 3 H catalyst under ultrasound irradiation was superior increased relative to the heating method.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Moreover, in an effort to seek improved yields, the catalytic amount of GO‐SiPr‐SO 3 H was screened (Figure ). As shown in this Figure, the 0.85 mol% (20 mg) of the catalyst showed the best result for compound 3 a (96 %, 3.5 min, TOF: 969 (h −1 ), (US irradiation); vs 68 %, 70 min, TOF: 6.9 (h −1 ) (heating method). The TOF of the GO‐SiPr‐SO 3 H catalyst under ultrasound irradiation was superior increased relative to the heating method.…”
Section: Resultsmentioning
confidence: 67%
“…The mechanism of the reaction was shown in Scheme and previously discussed . As shown in Scheme , two carbon‐carbon bonds were formed via C−H activation under metal‐free conditions and the aldehyde ring was connected to the phenol ring through carbon of carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the full details of preparation and characterization of the prepared catalysts are provided in supporting information of this paper. Previously, we have reported the synthesis of phenolic antioxidants using GO‐SO 3 H and RGO‐SO 3 H ,,. In this study, all of the catalysts were tested in the cyanosilylation of aromatic aldehyde using TMSCN and we found that the cyanosilylation of aldehydes could be rapidly accomplished.…”
Section: Resultsmentioning
confidence: 79%
“…The sulfonated reduced graphene oxide (RGO‐SO 3 H), sulfonated graphene oxide (GO‐SO 3 H) and graphene oxide (GO) were prepared based on previous work . The schematic representation of prepared catalysts was shown in Figure .…”
Section: Resultsmentioning
confidence: 99%